[quotation] 'We have to promote working on the land - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'We have to promote working on the land and make it professional. We have great potential, and still a lot of land to cultivate, but we have too many risks, low school attendance, not enough health centres and not enough safety' Professor Lala...